Study of the knowledge regarding reproductive health among the second PUC students from the colleges of Bangalore city - Menzil, Margaret; L. N., Deepa (International Journal Of Community Medicine And Public Health, 2018)
Background: According to an analysis by the World Bank and WHO, reproductive ill-health accounts for over 30% of the overall burden of disease and disability among women, compared with 12% for men. Reproductive health of adolescent girls is crucial since it determines the health of future generations to come. With this in background we conducted a study to find out the difference in the knowledge among the science and the non-science students and to find the relationship between the knowledge scores regarding the reproductive health with respect to select variables. Methods: A cross sectional study was done during July 2004 and January 2005, on 600 girl students (300 each from science and non-science stream) using a pre validated self administered questionnaire amongst II PUC students. Results: 68% science students knew that RTIs can be caused by unhygienic conditions, bacterial infections, STDs and unsafe abortions when compared to only 28% non-science students who knew the cause of RTIs. 64% Science students knew that the predominant routes of HIV transmission is unsafe sex, unsterilized instruments, contaminated blood transfusion, infected mother to child as compared to only 42% non-science students.74% science students knew that STDs can be prevented by use of condoms as compared to only 44.3% non-science students. Conclusions: The science students were found to be more knowledgeable than the non-science students.